CARBON EXCHANGE IN A TEMPERATE DECIDUOUS FOREST IN SOUTHERN ONTARIO - Parsaud, Ananta R. (My University, 2013)
Continuous measurements of carbon fluxes and meteorological variables were made at a newly initiated flux tower site at an oak-dominant temperate deciduous forest in Southern Ontario, Canada from January to December 2012. Results indicate this forest was a moderate carbon sink in 2012. Annual values of net ecosystem productivity (NEP), gross ecosystem productivity (GEP) and ecosystem respiration (R) were 263 ± 30, 1192 and 922 g C m-2, respectively. An unusual warm period in March caused a strong increase in R. Erratic peaks of daily air temperature in April also increased R. A drought in July and early August reduced NEP rates when soil moisture values reached the lowest point of the year in late July and early August (minimum 0.023 m3 m-3). This decrease in NEP was mostly caused by a decrease in GEP, rather than increased R. Water use efficiency at this deciduous forest was 2.86 g C kg-1 H2O, indicating conservative water use by the forest. Downwelling photosynthetic active radiation (PAR) was a dominant environmental control on photosynthesis, followed by air temperature and vapour pressure deficit, except in extreme dry periods when soil water stress affected carbon uptake. Extremely cloudy days in the growing season resulted in net carbon release due to low photosynthetic uptake values. Results indicate that large climatic fluctuations in this region may cause high instability in photosynthetic carbon uptake and release from soil carbon pools. This study helps to evaluate and quantify the responses of deciduous forests in the Great Lakes region to future climate change and extreme weather events.
Keywords: Carolinian forest; carbon balance; eddy covariance; temperate deciduous forest; net ecosystem productivity; Earth Sciences; Environmental Sciences; Earth Sciences